If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + 6) = 7x + -4 Reorder the terms: 4(6 + 2x) = 7x + -4 (6 * 4 + 2x * 4) = 7x + -4 (24 + 8x) = 7x + -4 Reorder the terms: 24 + 8x = -4 + 7x Solving 24 + 8x = -4 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 24 + 8x + -7x = -4 + 7x + -7x Combine like terms: 8x + -7x = 1x 24 + 1x = -4 + 7x + -7x Combine like terms: 7x + -7x = 0 24 + 1x = -4 + 0 24 + 1x = -4 Add '-24' to each side of the equation. 24 + -24 + 1x = -4 + -24 Combine like terms: 24 + -24 = 0 0 + 1x = -4 + -24 1x = -4 + -24 Combine like terms: -4 + -24 = -28 1x = -28 Divide each side by '1'. x = -28 Simplifying x = -28
| 45=60-y | | 4h-3(2-3h)=8h-2(4h+16) | | 19+y=25 | | -12x+76=2x+6 | | 9x-10y-4=0 | | 3m+n-20m+13n= | | 2t^2+9t-5=0 | | 10=7+t | | 4-3x+11= | | -6x^2=1 | | 6x^2=1 | | 30=12+t | | (.25)x+2=4-(.5)x | | 21+7x=105 | | 3.167x=4x-4 | | ax+bx-1=8 | | 3*6+3*5= | | 30*7=t | | 5x-6=13-x | | 18p^2-77p-18=0 | | 30t=7 | | 9(3x+10)=2x+340 | | 10=5t+10 | | 21+7x=19 | | 3.6+3.5= | | 3(x-2)=5(4+x) | | 2x^2-4x-18=0 | | 50(x-1)=36x | | -3=k+75 | | (-15)=3x+(-63) | | 5c-7=37 | | 7t=30 |